UKURAN KEPADATAN DAN POTENSI IKAN BARONANG TOMPEL (Siganus guttatus Bloch 1787) DI TELUK KOTANIA SERAM BAGIAN BARAT - Jacobus Latumeten (Universitas Pattimura, 2022)
Spotted rabbitfish (Siganus guttatus Bloch 1787) are valuable commercial fish species. Research on the fish species has been carried out in the waters of Kotania Bay, aiming to obtain information about size, density and potential of the fish species. Data are collected about total length (TL), weight and number of individual fish at four observation stations using 120m length of bottom gillnet with mesh size of 2.0, 2.5, 3.0 dan 3.5 inches. The bottom gillnet is operated in a circle that starting two hours before the low tide then the spotted rabbitfish caught are collected at the low tide. The results showed that the total length of the spotted rabbitfish is in the range of 11,3 – 33,9 cm which has dominated by fish with sizes of 18, 24 and 26 cm. Mean density of the fish is 209 individual/ha, so the abundance the fish in the area of seagrass beds 823.62 ha was estimated as 172.486 of fish individual, it’s 72,51% or 125.070 individuals are those fishes that has spawned for the first time. The mean weight of the spotted rabbitfish at this size is 533,51 grams, so calculated biomass is 66,73 tons and MSY value is 33,365 tons in wet season.